Adhesive material and support for adhesive material used in adhesive material
By designing a combination of specific tensile load and adhesive layers in the adhesion material, the problem of insufficient skin stretch inhibition and follow-up in the prior art is solved, and efficient trauma coverage and long-term attachment are achieved, promoting trauma healing and scarring are achieved. prevention.
Patent Information
- Application Number
- CN202411342938.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2015-05-20
- Filing Date
- 2016-03-17
- Publication Date
- 2024-12-20
AI Technical Summary
Existing hydrophilic colloidal adhesion materials and bandages are not effective in inhibiting skin stretching, and the support cannot stretch, resulting in low skin following and difficulty in long-term adhesion.
A sticker material for trauma coverage or postoperative trauma protection has been developed, with a tensile load of 13N/25mm or less in the length and width directions, a tensile load of 18N/25mm or more and 95N/ Materials below 25mm have excellent skin following and long-term adhesion. By adding specific materials such as woven fabrics and acrylic adhesives to the adhesive layer and support, the material is guaranteed to have low load load at low elongation. , the load becomes higher during stretching, adapting to the skin's stress changes.
This attachment material can effectively inhibit the stretching of the skin, improve the follow-up and adhesion of the skin, and long-term attachment, promote trauma healing, prevent the formation of scars and kelomas, and is suitable for trauma treatment after surgical surgery.
Smart Images

Figure BDA0005060218020000261 
Figure BDA0005060218020000271 
Figure BDA0005060218020000281
Abstract
Description
[0001] The present application is a divisional application, the application number of the parent application is 201680028810.5, the application date is 2016.3.17, and the title of the invention is: an attachment material, and an attachment material support body used in the attachment material. Technical Field
[0002] The present invention relates to a patch material, in particular a patch material for wound covering or postoperative wound protection, and further relates to a patch material for healing wounds, treating scars, or preventing the formation of scars / keloids, and a support for the patch material used therein. Background Art
[0003] Trauma or wounds caused by surgery usually heal in about two weeks, and then continue to change over about half a year. Generally speaking, scars become hard and red after about a month, and then slowly soften over several months, gradually becoming the same color as the surrounding skin. However, if the normal wound healing process is hindered for some reason, sometimes the wound will not heal and will become chronic or heal abnormally. One of the abnormal healing methods is called scars and keloids. The mechanism of scarring and keloids is still unclear, but it is also pointed out that it is related to the mechanical tension applied to the skin and the intensity of inflammation.
[0004] As a method for treating scars and preventing scar and keloid formation, a method of reducing the external force applied to the skin after trauma or surgery has been used (see Patent Documents 1 to 3). Specifically, Patent Document 1 discloses a hydrophilic colloid patch material with a specific elongation force. Patent Document 2 describes a device, a bandage, a kit and a method that are constructed in a manner to block the wound from being affected by internal stress and / or external stress, thereby improving the formation of scars and / or keloids. In addition, Patent Document 3 discloses a skin damage treatment body having an adhesive patch material, an elastomer for covering the affected part, and a supporting adhesive patch material, wherein the adhesive patch is attached to an area of the peripheral part adjacent to the affected part such as a keloid, and the supporting adhesive patch is attached in a manner that supports the elastomer from above and at least a portion of it covers the above adhesive patch, and the above elastomer is pressed toward the affected part.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-135582
[0008] Patent Document 2: Japanese Patent Application No. 2009-545382
[0009] Patent Document 3: Japanese Patent Publication No. 07-079827 Summary of the invention
[0010] Problem that the invention aims to solve
[0011] However, in the conventional hydrophilic colloid patches, bandages, and skin lesion treatment bodies, the skin's stretching is suppressed but the support body does not stretch, and therefore, there are disadvantages such as low followability to the skin and inability to be attached for a long time. Therefore, a scar / keloid prevention patch that can suppress the stretching of the skin, has excellent followability to the skin, and can be attached for a long time is desired. The subject of the present invention is to provide a patch for wound covering or postoperative wound protection that can suppress the stretching of the skin, has excellent followability to the skin, and can be attached for a long time, especially a patch for healing wounds, for treating scars, or for preventing scar / keloid formation. In addition, the subject of the present invention is to provide a patch support body suitable for making the aforementioned patch.
[0012] Methods used to solve problems
[0013] The invention for solving the above-mentioned problems is a patch material for wound covering or postoperative wound protection, wherein the 1% tensile load in the length direction and width direction of the patch material is below 13N / 25mm, and the 10% tensile load is above 18N / 25mm and below 95N / 25mm. The patch material of the present invention can suppress the stretching of the skin, and further, it is also excellent in the followability of the skin and can be attached for a long time. The long-term adhesion that the previous patch material of the patch material of the present invention does not fully possess is also excellent. The inventors and others found that if the 1% tensile load of the patch material is below 13N / 25mm and the 10% tensile load is above 18N / 25mm and below 95N / 25mm, such a patch material can appropriately and fully suppress the stretching of the skin according to the stress of wanting to stretch the skin, and is also excellent in the followability of the skin and can be attached for a long time. That is, the load of the patch material of the present invention is low at low elongation, and the load becomes high when stretched to a certain extent. Therefore, the patch material of the present invention has the following characteristics: it can stretch to fully follow the skin under weak stress that does not cause obvious impact on the wound area, and can be reliably fixed under strong stress that affects the wound area, thereby achieving the effect of healing wounds, treating scars or preventing scar / keloid formation.
[0014] That is, the gist of the present invention is as follows. It should be noted that in the present invention, "apparent density (g / cm 3 )” refers to the weight per unit volume of the attached material expressed in grams per cubic meter (g), which is the weight per unit area (g / m 2 ) divided by the thickness (μm).
[0015] [1] A patch for wound covering or postoperative wound protection, wherein the patch comprises a support and an adhesive layer provided on one side of the support, wherein the 1% tensile load in the length direction and the width direction of the patch is less than 13 N / 25 mm, and the 10% tensile load is greater than 18 N / 25 mm and less than 95 N / 25 mm.
[0016] [2] The patch according to [1], wherein the stiffness (rigidity and flexibility) (mm) of the patch according to a cantilever method is 5 mm or more and 40 mm or less.
[0017] [3] The patch according to [1] or [2], wherein the 5% tensile load in the longitudinal direction and the width direction of the patch is 5 N / 25 mm or more and 50 N / 25 mm or less.
[0018] [4] The patch according to any one of [1] to [3], wherein the stiffness (mm) and the apparent density (g / cm 3 ) is greater than 2 and less than 30.
[0019] [5] The patch according to any one of [1] to [4], wherein the support body comprises a woven fabric.
[0020] [6] The patch according to any one of [1] to [5], wherein the moisture permeability (g / m 2 24h) is 1,000g / m 2 ·More than 24h.
[0021] [7] The patch according to any one of [1] to [6], wherein the elongation recovery rate of the patch under a load of 9N or 18N in at least one of the longitudinal direction or the width direction is 85% or more.
[0022] [8] The patch according to any one of [1] to [7], which is used for healing wounds, treating scars, or preventing the formation of scars or keloids.
[0023] [9] The patch according to [8], which is used to heal wounds caused by surgical operations, to treat scars, or to prevent the formation of scars or keloids.
[0024]
[10] The patch material according to [9], wherein the surgical procedure is cesarean section, median sternotomy or laparoscopic surgery.
[0025]
[11] A patch material comprising a support and an adhesive layer provided on one surface of the support,
[0026] The 1% tensile load of the aforementioned patch material in the length direction and the width direction is less than 13N / 25mm, the 5% tensile load is greater than 5N / 25mm and less than 50N / 25mm, and the 10% tensile load is greater than 18N / 25mm and less than 95N / 25mm. The aforementioned support body comprises a woven fabric, and the aforementioned adhesive layer comprises a foamed acrylic adhesive. The aforementioned patch material is used to heal trauma caused by surgical operations, to treat scars, or to prevent the formation of scars and keloids.
[0027]
[12] A patch material comprising a support and an adhesive layer provided on one surface of the support,
[0028] The 1% tensile load of the aforementioned patch in the length direction and the width direction is less than 13N / 25mm, the 5% tensile load is greater than 5N / 25mm and less than 50N / 25mm, and the 10% tensile load is greater than 18N / 25mm and less than 95N / 25mm. The stiffness (mm) of the aforementioned patch is greater than 8mm and less than 25mm. The patch includes a shape having one or more concave or convex portions at the side clamped by both ends in the length direction or the width direction. The patch is used to heal trauma caused by surgical operations, to treat scars, or to prevent the formation of scars and keloids.
[0029]
[13] A support body for a patch material, which is used as a support body for a patch material for wound covering or postoperative wound protection, wherein the 1% tensile load in the length direction and the width direction of the support body is less than 13N / 25mm, and the 10% tensile load is greater than 15N / 25mm and less than 95N / 25mm.
[0030]
[14] A support for a patch material according to
[13] , wherein the support is a woven fabric using yarns having a total fineness of 40 dtex or more and 85 dtex or less, and having a warp density of 80 to 120 strands / inch (2.54 cm) and a weft density of 80 to 120 strands / inch (2.54 cm).
[0031]
[15] The patch support according to
[13] is a woven fabric using false twisted yarn having a total fineness of 40 dtex or more and 85 dtex or less and a stretch recovery rate (CR) of 15 to 40%.
[0032] Effects of the Invention
[0033] The patch material of the present invention can properly and fully inhibit the stretching of the skin, thus fully reducing the external force applied to the injured skin caused by trauma or surgery, and has excellent followability and adhesion to the skin, and can be attached for a long time. Therefore, the patch material of the present invention can promote the healing of wounds related to trauma or postoperative wounds, the treatment of scars, and effectively prevent the formation of scars and keloids.
[0034] Furthermore, the patch of the present invention relies largely on the physical properties of the support, and therefore the patch support of the present invention has strength and elongation suitable for obtaining the patch. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram of the shape of a patch material which is one embodiment of the present invention.
[0036] Figure 2 This is a schematic diagram of the shape of a patch material which is one embodiment of the present invention. DETAILED DESCRIPTION
[0037] Hereinafter, the present invention will be described in detail.
[0038] <Attached materials>
[0039] The patch material of the present invention (hereinafter also referred to as "the patch material") comprises a support body, and an adhesive layer provided on one side of the aforementioned support body. Furthermore, the patch material comprises a release body and / or a support body as required. In addition, one or more other layers may be sandwiched between the support body and the support body, between the support body and the adhesive layer, and / or between the adhesive layer and the release body. Details of the support body, adhesive layer, release body, support body, and other layers are described later. It should be noted that the direction along the long side of the patch material is recorded as the length direction, and the direction along the short side is recorded as the width direction. For example, in a rectangular patch material, the direction along the long side is recorded as the length direction, and the direction along the short side is recorded as the width direction. In the case of a square, the direction of one side is recorded as the length direction, and the other direction is recorded as the width direction. When the patch material is circular / elliptical, the same definition is applied. In the case of a roll, when cutting, the longer direction is recorded as the length direction, and the shorter direction is recorded as the width direction.
[0040] The 1% tensile load of the patch in the length direction and the width direction is less than 13N / 25mm, and the 10% tensile load is more than 18N / 25mm and less than 95N / 25mm. The patch material can appropriately suppress the stretching of the skin according to the stress of stretching the skin by having such physical properties, and has excellent followability to the skin, and can be attached for a long time. That is, the patch material of the present invention stretches for weak stress and fully follows the skin, and is reliably fixed for strong stress, thereby exerting the effect of healing wounds, treating scars, or preventing the formation of scars and keloids.
[0041] The aforementioned 1% tensile load is 13N / 25mm or less, preferably 11N / 25mm or less, more preferably 10N / 25mm or less, and further preferably 8N / 25mm or less. If the aforementioned 1% tensile load exceeds 15N / 25mm, the slight stretching of the skin is also suppressed, and the followability of the patch material to the skin may become insufficient. If the followability is insufficient, the discomfort during the patch becomes greater. The preferred range of the lower limit of the 1% tensile load is not specified, but is usually above 0.01N / 25mm.
[0042] The 5% tensile load is preferably 5N / 25mm to 50N / 25mm, more preferably 8N / 25mm to 50N / 25mm, and further preferably 8N / 25mm to 45N / 25mm. If the 5% tensile load is within the above numerical range, it is difficult to deform due to a moderate external force, and the effect of suppressing skin stretching becomes sufficient. In addition, the stretching of the skin can be suppressed, and the patch material in the state of being attached is also excellent in the followability of the skin, and discomfort and skin irritation are not easy to occur during the attachment.
[0043] The aforementioned 10% tensile load is 18N / 25mm or more and 95N / 25mm or less, preferably 20N / 25mm or more and 85 / 25mm or less, more preferably 25N / 25mm or more and 80N / 25mm or less, and further preferably 30N / 25mm or more and 80N / 25mm or less. If the aforementioned 10% tensile load is lower than 18N / 25mm, the effect of suppressing strong external forces of the patch material becomes insufficient, and the skin may be stretched significantly. In addition, if the aforementioned 10% tensile load exceeds 95N / 25mm, although the stretching of the skin can be suppressed, in the state where the patch material is attached, sometimes the tracking of the patch material to the skin is significantly reduced, and there is discomfort during the attachment and it is difficult to perform normal actions, or the adhesion is deteriorated, or skin irritation occurs. It should be noted that the tensile load in the present invention is measured by performing a tensile test according to JIS K 7113, and the measurement of 1%, 5% and 10% tensile loads is implemented.
[0044] The elongation recovery rate of at least one of the length direction or width direction of the patch material under 9N and 18N load is preferably 85% or more. The patch material can appropriately suppress the stretching of the skin according to the stress of stretching the skin as described above, and the elongation recovery rate that can be restored to the original length after the stress applied to the skin disappears is 85% or more. The elongation recovery rate is preferably 85% or more, more preferably 90% or more. Even if the patch material is temporarily stretched due to the stress applied to the skin, it can be restored to a length close to the original length, rather than presenting a state of being stretched all the time, and therefore, the effect of suppressing the stretching of the wound part can be maintained for a long time.
[0045] In this patch material, the stiffness (mm) based on the cantilever method is preferably 5mm or more and 40mm or less. By having the aforementioned tensile load characteristics and having the stiffness (mm) based on the cantilever method of 5mm or more and 40mm or less, this patch material can appropriately suppress the stretching of the skin, fully reduce the external force applied to the injured skin caused by trauma or surgery, and also has excellent followability to the skin and can be attached for a long time. The stiffness (mm) based on the cantilever method of this patch material is preferably 5mm or more and 40mm or less, more preferably 8mm or more and 25mm or less, and further preferably 10mm or more and 20mm or less. In the patch material, if the stiffness (mm) based on the cantilever method is within the aforementioned numerical range, the followability to the skin and the effect of suppressing the stretching of the skin become sufficient.
[0046] In this patch material, the stiffness (mm) and apparent density (g / cm 3 ) is preferably greater than 2 and less than 30. The inventors of the present invention have found that: for the patch material, the product value of the stiffness and the apparent density is also closely related to the effect of inhibiting skin stretching when the patch material is attached to the skin and the long-term adhesion, especially the long-term adhesion. In the patch material, the product of the stiffness and the apparent density is preferably greater than 2 and less than 30, more preferably greater than 3 and less than 25, further preferably greater than 6 and less than 22, and particularly preferably greater than 8 and less than 15. If the product of the stiffness and the apparent density is within the above-mentioned numerical range, the followability and long-term adhesion to the skin are excellent. Here, the "stiffness based on the cantilever method (mm)" can be measured in accordance with JIS L 1096.
[0047] The moisture permeability of the patch material is preferably 1,000 (g / m 2 · 24h) or more. By making the moisture permeability of the patch material 1,000 (g / m 2· 24h) or more, the feeling of stuffiness when attached to the skin is small, and it is not easy to cause skin irritation or itching during attachment, so it can be attached for a long time. The moisture permeability of the attachment material is more preferably 2,000 (g / m 2 ·24h) or more, more preferably 3,000 (g / m 2 ·24h) or more, particularly preferably 5,000 (g / m 2 ·24h) or more, and most preferably 9,000 (g / m 2 The higher the moisture permeability, the more preferred it is. The preferred upper limit of moisture permeability is not specified, but is usually 30,000 (g / m 2 ·24h) or less. It should be noted that in the present invention, the measurement of moisture permeability is carried out according to the B condition of JIS Z0208 at a temperature of 40°C and a relative humidity of 90%. That is, one side of the patch material is adjusted to a temperature of 40°C and a relative humidity of 90%, and a moisture absorbent such as calcium chloride is placed on the other side to absorb the moisture passing through the patch material, and the weight change of the moisture absorbent is converted into a value of 24 hours, an average of 1m 2 to calculate.
[0048] This patch material suppresses the stretching of the skin by making each tensile load, the elongation recovery rate during load, the stiffness based on the cantilever method, the product of the stiffness based on the cantilever method and the apparent density, and the moisture permeability within the aforementioned specified range, and has excellent long-term adhesion. That is, it can effectively prevent the skin injured by trauma or surgery from being deformed due to mechanical effects such as the stretching of external force and scar tissue, and therefore, it is effective as a healing purpose of wounds, a therapeutic purpose of scars, and a scar / keloid formation prevention purpose. In addition, this patch material is also excellent in the followability of the skin. In addition, the moisture permeability of this patch material is also excellent, and therefore, it is not easy to be stuffy when attached to the skin, and can be attached for a long time. For being able to attach for a long time, there are influences such as excellent followability of the skin, sufficient adhesion, discomfort during attachment, less skin irritation and itching.
[0049] The thickness of the patch is not particularly limited, but is 6 μm to 6 mm, preferably 50 μm to 2 mm, more preferably 60 μm to 1 mm, and even more preferably 80 μm to 0.5 mm, from the viewpoint of ease of handling.
[0050] The shape of the patch material is not particularly limited as long as it has the aforementioned support and adhesive layer, and can be made into a free shape that matches the purpose, such as a rectangular, square, rhombus or other quadrilateral, a polygon, an ellipse, a sheet-like shape formed by a proper combination of these shapes, a strip-like shape formed continuously along a specific direction, a roll-like shape, etc. For patch materials having corners around, R can be appropriately set at the corners around. In addition, cuts, slits, etc. are three-dimensionally formed or set in accordance with the part to be attached. It should be noted that when a shape is made in which concave and convex parts are set along the length direction or the width direction, and the side part clamped by the two ends in the length direction or the width direction has more than one concave or convex part, and the corners are increased, there are advantages such as difficulty in peeling and improved adhesion due to the dispersion of the stress when the skin is stretched and contracted. For example, it is preferably made into a dumbbell shape (a shape such as the longitudinal section of a dumbbell; refer to Figure 1 and 2 ), a wave-shaped (the edge of the attached material is cut into a wave-shaped) shape. In particular, by making Figure 1 and 2 The shapes obtained by cutting arc-shaped cuts into the upper and lower front end parts of the dumbbell shape, as shown in the figure, and the shapes having one or more concave or convex parts on the sides clamped by the two ends in the length direction and the width direction can be difficult to peel off in both the length direction and the width direction. The size of these adhesive materials can also be freely selected according to the purpose, but in order to prevent the formation of scars and keloids, etc., when attached to the wound caused by the skin, it is necessary to have a size that can fully cover the wound. For example, as an adhesive material for cesarean section wounds, as an adhesive material for wounds longer than the length (in most cases, in the range of 5cm to 15cm), the width is preferably 3cm to 8cm, and the length is preferably about 5cm to 25cm.
[0051] When the patch is used for medical purposes such as preventing scars / keloids, or being attached to wounds on the skin, it can be sterilized to prevent bacterial infection, viral infection, etc. As the aforementioned sterilization method, methods commonly used for patch materials can be used, such as gamma ray sterilization, electron beam sterilization, high pressure steam sterilization, ethylene oxide gas sterilization, etc.
[0052] The patch material can also be preferably applied from its top to administer the medicament required for the affected part such as wounds. This is because: there is no need to peel off and replace the patch material each time the affected part is administered, so the patient's QOL can be improved, and a patch material can be used continuously for a long time. As the medicament applied from the patch material, it is not particularly limited, and it is preferably a medicament that improves the effect of the present invention. For example, antibacterial agents, anti-inflammatory analgesics, steroids, anesthetics, antifungals, vitamins, etc. can be listed. These medicaments exert their effects in the whole body or locally by percutaneous absorption, or exert their effects locally at the attachment site.
[0053] From the viewpoint of healing wounds, treating scars, preventing scars / keloids, etc., the patch material preferably blocks ultraviolet radiation to the wound part. The ultraviolet transmittance of the patch material in the wavelength range of 280 to 400 nm is preferably 20% or less, more preferably 15% or less, and particularly preferably 10% or less.
[0054] In a preferred embodiment of the present invention, as the above-mentioned agent, an agent that inhibits the formation of scars and keloids may be contained. Such agents include antiallergic agents, steroid agents, TGF-β signal blockers, etc. It is known that allergic reactions interfere with the occurrence / aggravation of scars and keloids, itching, pain and other symptoms. In addition, adrenal corticosteroids have a variety of effects, but for the skin, they have the effect of inhibiting inflammation, the effect of atrophying tissue, etc. It is known that TGF-β plays a very important role in maintaining the homeostasis of the organism, but it can cause various diseases such as scleroderma, sclerosis of the skin, and various fibrotic diseases due to abnormal TGF-β signals. As a common cause of these diseases, it is considered that excessive tissue fibrosis is induced by excessive TGF-β signals.
[0055] Hereinafter, the support, the adhesive layer, the release body, the carrier, and other layers constituting the patch will be described in detail.
[0056] [Supporting body]
[0057] The support body of the patch material of the present invention (hereinafter also referred to as "the support body") is not particularly limited as long as the 1% tensile load in the length direction and the width direction when the patch material is made is 13N / 25mm or less and the 10% tensile load is 18N / 25mm or more and 95N / 25mm or less, and examples thereof include support bodies formed from the following raw materials.
[0058] The raw material of the support may be selected from:
[0059] Polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate;
[0060] Nylon (nylon 6, nylon 66) and other polyamides;
[0061] Polyolefins such as polypropylene, polyethylene, low-density polyethylene (LDPE), and high-density polyethylene (HDPE);
[0062] Olefin copolymers such as ethylene-vinyl acetate copolymer (EVA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl acrylate copolymer (EMA), ethylene-methyl methacrylate copolymer (EMMA), and ethylene-acrylic acid copolymer (EAA);
[0063] Polyvinyl alcohol (PVA);
[0064] Polychlorinated compounds such as polyvinyl chloride and polyvinylidene chloride;
[0065] Pulp made from wood etc. as raw materials;
[0066] Silicones;
[0067] Polyurethane, etc., or composite materials thereof. In addition, materials that have low moisture permeability when they exist alone may be made porous by including calcium carbonate, etc., or processed by perforation, etc. for use.
[0068] As the raw material of the support, polyester, polyamide, polyolefin, polyurethane are preferred among these, and polyethylene terephthalate (PET), nylon, polyethylene, pulp are more preferred, and polyethylene terephthalate (PET), nylon, low-density polyethylene (LDPE) is further preferred. In addition, as a composite raw material, a composite raw material of polyethylene terephthalate (PET) and pulp is preferred.
[0069] In addition, the support body may include a woven fabric formed from the above-mentioned raw materials, and may also include a non-woven fabric, a knitted fabric, a film, a foam, etc. Among these, the support body preferably includes a woven fabric from the viewpoint that the patch material has sufficient moisture permeability, that the agent can be applied from the patch material when attached, and that the patch material is stretched by following a small movement when attached (a 1% tensile load is small) but the movement that affects the formation of scars / keloids is suppressed (a 10% tensile load is large). The PET film has a large 1% tensile load, and most of them will not follow the small movement when attached, and feel uncomfortable or easy to peel off when attached. Non-woven fabrics follow small movements when attached, but most of them will not suppress the movement that affects the formation of scars / keloids (a 10% tensile load is small).
[0070] In addition, about this support, the woven fabric, nonwoven fabric, knitted fabric, film, foam etc. formed by the aforementioned raw materials can be further processed. For example, it can be coated with polyurethane resin, acrylic resin etc., and it is also possible to laminate with polyurethane film etc. By coating or laminating etc., a layer with flexibility is set between the support and the adhesive layer, which can reduce physical stimulation and not hinder the fine movement of the skin. And then, even when the attached material is stretched due to external force etc., it will not stretch completely, and can be restored to the original state or can prevent the infiltration of water etc. when attached.
[0071] As the support, there can be used polyurethane-coated PET woven fabric, acrylic-coated PET woven fabric, PET woven fabric laminated with a polyurethane film, PET woven fabric laminated with an ether polyurethane film, a nonwoven fabric formed from a composite material of PET and pulp, an LDPE film, an acrylic-coated nylon woven fabric, or a polyurethane foam.
[0072] The characteristic that this patch material has is relatively large to the dependence part of the physical characteristic that this support body has.Especially, in order to suitably and fully bring into play the effect of suppressing skin stretching, the 1% tensile load of the length direction and width direction of this support body needs to be below 13N / 25mm, and the 10% tensile load needs to be above 15N / 25mm and below 95N / 25mm.By using the support body of different composition and characteristic of length direction and width direction, the support body of different strength of length direction and width direction can be made.This support body is by possessing such physical strength, and the physical strength of the obtained patch material also becomes appropriate, is difficult to be deformed because of the stretching of external force, scar tissue, etc., can effectively suppress the stretching of skin.Tensile strength is not only limited to the type of support body, if use woven fabric, then be easy to adjust to 1% tensile load is below 15N / 25mm, 10% tensile load is above 15N / 25mm and below 95N / 25mm.
[0073] The support is particularly preferably a woven fabric using yarns having a total fineness of 40 dtex or more and 85 dtex or less, and having a warp density of 80 to 120 strands / inch (2.54 cm) and a weft density of 80 to 120 strands / inch (2.54 cm).
[0074] If the total fineness is less than the aforementioned lower limit, the woven fabric tends to be thin and difficult to handle. If the total fineness is greater than the aforementioned upper limit, the woven fabric tends to be too thick and the followability to the skin tends to deteriorate when made into a patch.
[0075] If the weaving density is less than the lower limit, the material tends to fall off and the sense of hardness tends to disappear, while if the weaving density is greater than the upper limit, the feeling of adhesion tends to deteriorate.
[0076] In addition, the yarn used in the support is preferably a false twisted yarn (false twisted system) having a stretch recovery rate (CR) of 25 to 60%. If the stretch recovery rate is less than the lower limit, there is a tendency for the 1% tensile load to become larger, and if the stretch recovery rate is greater than the upper limit, there is a tendency for the 10% tensile load to become smaller. In addition, the strength of the false twisted yarn is preferably 3 to 6 cN / dtex, and the elongation is preferably 15 to 40%.
[0077] As the support, a plain knitted fabric (plain woven fabric) using polyester false twisted yarn is more preferable.
[0078] The support body is obtained by weaving by a conventional method and performing post-treatment such as heat setting according to the purpose.
[0079] It should be noted that the 1% tensile load of this support is below 13N / 25mm, preferably below 11N / 25mm, more preferably below 10N / 25mm, and further preferably below 8N / 25mm. If the aforementioned 1% tensile load exceeds 13N / 25mm, the slight stretching of the skin is also suppressed, and the resulting patch material may not be sufficient for the followability of the skin. If the followability is insufficient, the discomfort in the patch becomes larger. The preferred range of the lower limit of the 1% tensile load is not specific, and is usually more than 0.01N / 25mm.
[0080] The 5% tensile load of this support is preferably more than 5N / 25mm and less than 50N / 25mm, more preferably more than 8N / 25mm and less than 50N / 25mm, further preferably more than 8N / 25mm and less than 45N / 25mm. If the aforementioned 5% tensile load is within the aforementioned numerical range, then it is difficult to be deformed because of moderate external force etc., and the effect of the suppression of skin stretching of the obtained patch material becomes sufficient. In addition, the stretching of skin can be suppressed, and the followability of skin is also excellent, and it is difficult to produce discomfort and skin irritation in the patch.
[0081] The 10% tensile load of the support is 15N / 25mm or more and 95N / 25mm or less, preferably 20N / 25mm or more and 80N / 25mm or less, more preferably 25N / 25mm or more and 80N / 25mm or less, and further preferably 30N / 25mm or more and 80N / 25mm or less. If the aforementioned 10% tensile load is lower than 15N / 25mm, the effect of the obtained patch material in suppressing strong external forces, etc. becomes insufficient, and it is possible to greatly stretch the skin. In addition, if the aforementioned 10% tensile load exceeds 95N / 25mm, although the stretching of the skin can be suppressed, in the state of the patch material being attached, the following of the patch material to the skin is sometimes significantly reduced, and there is discomfort during the attachment and it is difficult to perform normal actions or produce skin irritation.
[0082] The breaking strength of the support is preferably 18 N / 25 mm or more, more preferably 50 N / 25 mm or more, and even more preferably 100 N / 25 mm or more.
[0083] The support may be added with commonly used additives as required. Examples of the aforementioned additives include ultraviolet absorbers, antioxidants, fillers, pigments, colorants, flame retardants, antistatic agents, and the like. One of these additives may be used, or a plurality of these additives may be used in combination. The content of these additives may be selected in the optimal range according to the type of additive, and is usually set to 0.001 to 30% by mass, preferably 0.01 to 25% by mass, and more preferably 0.1 to 20% by mass in the support layer. From the viewpoint of healing wounds, treating scars, preventing scars / keloids, etc., the support preferably adds an ultraviolet absorber to the support layer or applies the ultraviolet absorber to the support layer, etc., so as to block the irradiation of the wound with ultraviolet rays. The ultraviolet transmittance of the support in the range of wavelengths of 280 to 400 nm is preferably 20% or less, more preferably 15% or less, and particularly preferably 10% or less.
[0084] As the thickness of the support, from the viewpoint of giving full play to the effect of suppressing skin stretching and improving the handling property of the patch material of the present invention, it is 5 μm or more and 5 mm or less, preferably 20 μm or more and 3 mm or less, more preferably 40 μm or more and 1 mm or less, further preferably 50 μm or more and 0.5 mm or less, and particularly preferably 60 μm or more and 0.15 mm or less. If the thickness of the support is within the aforementioned numerical range, the effect of suppressing skin stretching of the patch material is easily obtained, and it is impossible to be damaged by friction, etc. during use. In addition, due to the excellent handling property, it is difficult to produce discomfort when attached to the skin, and it is especially excellent in tracking property for the curved surface of the skin, so it is difficult to peel off from the skin.
[0085] In order to apply ointments, pastes, gelling agents, etc. containing drugs from the support body during the patch, the support body may be provided with micropores. For example, by applying an ointment containing a steroid agent from the support body, inflammation and itching of the wound site can be suppressed without causing the patch material to peel off. The size of the micropores is not particularly limited as long as the ointment, paste, or gelling agent is large enough to penetrate the wound site, and is preferably 0.01 to 30 mm. 2 .
[0086] [Adhesive layer]
[0087] The adhesive layer of the patch material of the present invention (hereinafter also referred to as "the adhesive layer") is arranged on the single side of the aforementioned support. The adhesive layer plays a role in fixing the patch material of the present invention in a manner that it can be removed from the skin. The adhesive layer comprises at least one adhesive. In addition, any components such as a softener, a tackifier, a pH regulator, a medicinal ingredient, a filler, an antioxidant (antioxidant, preservative), a coloring material, and a fragrance may also be included as required. Below, the adhesive and the aforementioned arbitrary components included in the adhesive layer are described in detail.
[0088] The type of adhesive contained in the adhesive layer is not particularly limited, and examples thereof include urethane adhesives, acrylic adhesives, rubber adhesives, silicone adhesives, and the like.
[0089] As the urethane adhesive, there can be mentioned an adhesive comprising a urethane resin obtained by reacting a polyol with a polyisocyanate compound. As the polyol, there can be mentioned, for example, polyether polyol, polyester polyol, polycarbonate polyol, polycaprolactone polyol, etc. As the polyisocyanate compound, there can be mentioned, for example, diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, etc.
[0090] In order to suppress gelation during the reaction and increase the adhesive strength, the NCO / OH molar ratio of the polyol and the polyisocyanate compound used in the above reaction is preferably 0.7 / 1.00 to 1.00 / 1.00.
[0091] The production of urethane adhesives can be carried out by common methods such as bulk polymerization (solid state reaction) method and solution polymerization method in which the reaction occurs in a molten state. As the solvent used in the solution polymerization method, specifically, ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as dioxane and tetrahydrofuran; glycol ether solvents such as cellosolve and carbitol; glycol ether solvents such as cellosolve acetate; amide solvents such as dimethylacetamide and dimethylformamide; aromatic hydrocarbon solvents such as toluene and xylene; alcohol solvents such as methanol, ethanol, and isopropanol; and mixed solvents thereof.
[0092] When manufacturing a urethane adhesive, a catalyst and an additive may be used as needed. Examples of the catalyst include nitrogen-containing compounds such as triethylamine and triethylenediamine; and common urethane-forming catalysts such as organic metal compounds such as dibutyltin dilaurate, tin octoate, and tin stearate. Examples of the additive include ultraviolet absorbers such as substituted benzotriazoles, antioxidants such as phenol derivatives, and anti-hydrolysis agents.
[0093] In order to improve the cohesive force of urethane adhesives and avoid problems such as residual glue, chain extenders can be used in the manufacture of the above-mentioned urethane adhesives. Furthermore, urethane adhesives can be used in combination with polyisocyanate curing agents to change the adhesive properties. It is effective to improve the adverse conditions such as residual glue by using polyisocyanate curing agents in combination to improve cohesive force. As the polyisocyanate used as a curing agent, the polyisocyanate used in the above-mentioned reaction can also be used, preferably the polyol adduct of isocyanate obtained by their reaction with difunctional or higher polyols, in addition, polymerized polyisocyanates, isocyanurate modified bodies, carbodiimide modified bodies are also preferably used. Specifically, Coronate L, Coronate HL, Coronate 3041, Coronate 2030, Coronate 2031, Coronate HX, Millionate MTL, Millionate MR, etc. manufactured by Japan Polyurethane Industry Co., Ltd. can be listed.
[0094] Urethane adhesives are highly safe and are practical as medical polymer materials. They have high moisture permeability, good adhesion to the skin, are soft and have good fusion properties, and form adhesives with low irritation. Therefore, they are suitable for use in attaching to the human body and are suitable as adhesives for medical patch materials. In addition, they all meet the requirements of adhesion, safety, stability as a material, and economy.
[0095] Examples of acrylic adhesives include homopolymers of acrylic acid esters or methacrylic acid esters having an alkyl group with a carbon number of 4 to 12, such as butyl acrylate, isononyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, isooctyl acrylate, and n-octyl acrylate; copolymers obtained by copolymerizing these (meth) acrylic acid esters as main components with one or more other monomers such as (meth) acrylic acid, vinyl acetate, vinyl pyrrolidone, acrylamide, hydroxyethyl acrylate, and hydroxypropyl acrylate. Other monomers are usually used in a range of 2 to 50% by mass.
[0096] Acrylic adhesives can be obtained by using peroxides such as benzoyl peroxide as initiators in organic solvents such as toluene, hexane, and ethyl acetate, and polymerizing monomers under a nitrogen atmosphere. The acrylic adhesive obtained by this method is called a solvent-type acrylic adhesive. In addition, an emulsion-type acrylic adhesive obtained by emulsifying and dispersing the monomers in water with an emulsifier and then polymerizing can also be used.
[0097] In order to crosslink the acrylic adhesive, after polymerization, a crosslinking agent such as a polyisocyanate crosslinking agent, a polyepoxy resin crosslinking agent, or a polyvalent metal crosslinking agent is used to crosslink the acrylic adhesive. Specifically, for example, Tetrad-X (manufactured by Mitsubishi Gas Chemical Co., Ltd.), Nathem (manufactured by Nippon Chemical Industry Co., Ltd.), Coronate HL, Coronate L, Coronate EH (manufactured by Nippon Polyurethane Industries Co., Ltd.), etc. can be used. These crosslinking agents are usually added to the adhesive composition when it is prepared.
[0098] By cross-linking the acrylic adhesive to impart cohesion, a structure can be made that maintains moderate adhesive force on the skin surface and leaves no adhesive residue when peeled off from the skin. The cross-linking agent is generally used in the range of 0.01 to 5 parts by mass, preferably 0.05 to 2 parts by mass, relative to 100 parts by mass of the acrylic adhesive (acrylic polymer component). That is, the amount of the cross-linking agent is appropriately selected from the aforementioned range in consideration of adhesive properties, cohesion, exudation of the medicinal ingredient, etc. The acrylic adhesive may also be formulated with a liquid component such as a softener as needed.
[0099] As rubber-based adhesives, adhesives obtained by adding tackifiers such as rosin-based resins, terpene-based resins, coumarone-indene resins, and petroleum-based resins to rubber-like elastic bodies such as natural rubber, styrene-isoprene-styrene block copolymers, polyisobutylene, polybutene, polyisoprene, and mixtures of two or more of these can be listed. Softeners such as liquid polybutene, liquid polyisobutylene, and mineral oil; fillers such as titanium oxide and zinc oxide; antioxidants such as butylated hydroxytoluene, etc. can be added to the rubber-based adhesive as needed. Among these, from the viewpoint of adhesion, adhesives using styrene-isoprene-styrene block copolymers as the main base are preferred.
[0100] As silicone adhesives, for example, mixtures or partial condensates of silicone rubber and silicone resin can be cited. As silicone rubber, high molecular weight straight-chain polydiorganosiloxanes having silicon functional groups such as silanol groups at both ends can be cited, and as silicone resins, polyorganosiloxanes having branched or network structures containing monofunctional siloxane units and tetrafunctional siloxane units and having silicon functional groups such as silanol groups or methoxy groups in the molecules can be cited. More specifically, as such silicone rubber, long-chain copolymers of polydimethylsiloxane can be cited, and as silicone resins, MQ resins (silicone resins having a three-dimensional structure of M units ((CH3)3SiO1 / 2) and Q units (SiO2)) can be cited.
[0101] The composition ratio of silicone rubber / silicone resin constituting the silicone adhesive is not particularly limited, but is preferably 30:70 to 60:40, and more preferably 35:65 to 45:55 (mass ratio). In the present invention, particularly preferred composition ratios of silicone rubber / silicone resin include 40 / 60 (w / w) (BIO-PSA4501, Dow Corning), 45 / 55 (w / w) (BIO-PSA4601, Dow Corning), and the like.
[0102] Silicone adhesives are adhesives that have pressure-sensitive adhesive properties due to the silicon functional groups present in the molecules. As organic groups bonded to silicon atoms, various monovalent hydrocarbon groups such as methyl, ethyl, vinyl, and phenyl can be listed, and the adhesiveness can be adjusted by selecting the type of substituent. Silicone adhesives have high air permeability and moisture permeability due to the large intermolecular distance of polyorganosiloxane as its main component.
[0103] As the adhesive included in this adhesive layer, various adhesives can use 1 kind alone, and also can use more than 2 kinds.In addition, as the form of these adhesives, can only use adhesive, also can be used as the hydrophilic colloid adhesive of the form of the hydrophilic gel that for example makes the hydrophilic gel that comprises water, the organogel that comprises organic solvent, the hydrophilic colloid adhesive of the hydrophilic colloid that makes the hydrophilic polymer compound be added.The adhesive layer can be formed with the form of single adhesive, and also can be formed by stacking a plurality of adhesive layers.When being stacked with a plurality of adhesive layers, can be stacked with a plurality of adhesives of different kinds, or be stacked with adhesives of different sizes.For example, can use the hydrophilic colloid adhesive smaller than support body as the pad part of band-aid.
[0104] Among these pressure-sensitive adhesives, acrylic pressure-sensitive adhesives or foamed acrylic pressure-sensitive adhesives are preferred, and foamed acrylic pressure-sensitive adhesives are more preferred, from the viewpoints of moisture permeability, low irritation, safety, and moderate adhesiveness.
[0105] The adhesive layer may contain a softener, a tackifier, a pH adjuster, a medicinal ingredient, a filler, an antioxidant (antioxidant, preservative), a colorant, and a flavor as optional components.
[0106] The softener reduces the elasticity of the adhesive to impart flexibility and improves adhesion, so it can be added as needed. Examples of the softener include mineral oils such as mobile paraffin, mobile isoparaffin, and cycloparaffin oil; vegetable oils such as olive oil and olive squalane; animal oils such as lanolin, tall oil, and beeswax; and synthetic oils such as fatty acid triglycerides and silicone oil.
[0107] Tackifiers can impart appropriate flexibility to adhesives and are less prone to cohesive failure, so they can be added as needed. Examples of tackifiers include natural rosin derivatives, coumarone-indene resins, terpene oligomers, aliphatic petroleum resins, alkyl-modified phenolic resins, polyterpene resins, gum rosin, rosin esters, oily phenolic resins, coumarone-indene resins, and petroleum hydrocarbon resins.
[0108] The type of pH adjuster is not particularly limited unless the purpose of the present invention is impaired, and examples thereof include karaya gum, citric acid, phosphoric acid, sodium hydrogen phosphate, anhydrous sodium hydrogen phosphate, pectin, anhydrous citric acid, alkali metal hydroxides, organic acid buffers, etc. By using these pH adjusters, the pH of the adhesive layer can be adjusted to a range of 4.0 to 6.0 in accordance with the pH of normal skin.
[0109] The medicinal component that can be contained in the adhesive layer is not particularly limited, but is preferably a component that enhances the effect of the present invention. Specific examples include the same drugs as those exemplified as drugs that can be administered from the patch.
[0110] The thickness of the adhesive layer is not particularly limited, but is preferably 1 μm to 1 mm, more preferably 10 μm to 0.5 mm, and even more preferably 20 μm to 0.1 mm, from the viewpoint of ensuring fixation to the skin and balancing the thickness of the support. It should be noted that the coating weight (adhesive thickness) of the adhesive layer when dry is preferably 1 g / m 2 Above and 1000g / m 2 Less than 10 g / m 2 Above and 200g / m 2 Below, more preferably 20g / m 2 Above and 100g / m 2 If the thickness or coating weight of the adhesive layer is above the upper limit, the moisture permeability and handling properties may be reduced. On the other hand, if it is below the lower limit, the fixation to the skin may not be ensured.
[0111] The adhesive force of such a pasting material having an adhesive layer on one side is preferably neither too strong nor too weak, and the adhesive force to the BA-SUS plate is set to about 0.3 to 10N / 25mm, preferably 0.5 to 4.0N / 25mm. It should be noted that regarding the aforementioned adhesive force to the BA-SUS plate, a tape test piece cut into a length of 150mm and a width of 25mm was attached to the BA-SUS plate at a temperature of 23°C and an atmosphere of 50% RH, and a 2kg rubber roller was used to press it back and forth at a speed of 600mm / min. The peeling force was measured within 1 minute, the peeling angle was 180 degrees, and the peeling speed was 300mm / min, and the adhesive force of the test piece to the BA-SUS plate was calculated. The measurement was performed 3 times, and the average value was used as the adhesive force of the pasting material to the BA-SUS plate (unit: N / 25mm).
[0112] In addition, the adhesive layer provided on the support has a viscosity that is neither too strong nor too weak, and the probe adhesion is set to about 0.4 to 10 (N / 5mmφ), preferably about 0.6 to 5.0 (N / 5mmφ). It should be noted that the above-mentioned probe adhesion is measured using a probe adhesion tester manufactured by NICHIBAN based on a probe adhesion test method described with reference to JIS Z0237. The measurement is performed 3 times, and the average value is used as the probe adhesion (unit = N / 5mmφ).
[0113] [Stripping body]
[0114] The peeling body used in the patch material of the present invention (hereinafter also referred to as "the peeling body") is provided in a peelable state on the opposite side of the side provided with the support body in the adhesive layer for the purpose of protecting the adhesive layer. As the peeling body, peeling paper, peeling film, etc. commonly used in the field of patch materials can be used. For example, paper substrates such as high-quality paper, glass paper, polyester film, etc. treated with silicone release can be used. In addition, the thickness of the peeling body is not particularly limited, usually more than 20μm, preferably more than 40μm, and its upper limit is about 500μm. By providing one or more linear peeling body separation parts that break its outer shape at the approximate center of the peeling body, even if one peeling body is peeled off, the other peeling bodies will remain, and the sticking operation can be performed without contacting the adhesive surface, and the operability is improved. When the patch material is made into a roll, it is particularly easy to peel off the peeling body, which is effective for improving the handling property. In addition, in order to easily peel off two or more peeling bodies from the adhesive, the peeling body can be configured in a way that covers one or folds back.
[0115] [Carrier]
[0116] The carrier used in the patch material of the present invention (hereinafter also referred to as "the carrier") is arranged in a peelable state on the opposite side of the surface of the support body provided with the adhesive layer, and exerts the effect of enhancing the support body and improving the manufacturability and operability of the patch material of the present invention. In addition, considering that the visibility such as the attachment position can be confirmed when attaching, it is expected that the carrier is transparent or translucent. And then, the carrier has a relatively high elastic modulus for the support body, preferably an elastic modulus of about 3 to 20 times for the support body. In addition, it is necessary to ensure the appropriate adhesion between the carrier and the support body to stack the surface of the support body, and therefore, it is appropriate to carry out various treatments in advance. As such treatment, for example, corona treatment, plasma treatment, ultraviolet treatment, roughening treatment, etc. can be listed.
[0117] When the carrier is difficult to peel off from the support, a cut can be set near the central part of the carrier, or the cut intervals of the carrier can be separated and the carrier can be made into 2. In addition, a laminated band or film on the cut of the carrier can be further provided, and a handle can be provided in the form of a grip sheet. The handle can be made into a film, a nonwoven fabric, a woven fabric or their laminate, or an adhesive tape, and can also be colored. The end of the carrier can be made into a wavy shape or a state with a plurality of cuts, or a carrier formed larger than the support can be used. Even when the attached material is made into a roll, it is also easy to peel off the carrier, which is effective for improving the handling property.
[0118] The material used as the support includes, for example, polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate, polyamides such as nylon, polyvinyl chloride, polyvinylidene chloride, etc. In addition, not only the supports of these monomers but also the supports of composites obtained by laminating them with paper, nonwoven fabrics, woven fabrics, knitted fabrics, or metal foils may be used. From the viewpoints of visibility, cost, etc., polyolefin and polyester films are preferably used as such supports.
[0119] The thickness of the support is not particularly limited, but is usually 20 μm or more, preferably 40 μm or more, and the upper limit thereof is approximately 500 μm.
[0120] In the patch material of the present invention, one or more other layers may be sandwiched between the carrier and the support, between the support and the adhesive layer, and / or between the adhesive layer and the release body. For example, in order to improve adhesion and release properties, a primer layer, an adhesive layer or a release agent layer may be provided, or a film, nonwoven fabric, woven fabric, or a laminate thereof may be sandwiched.
[0121] <Method for producing patch material>
[0122] The method for producing the patch is not particularly limited, and the patch can be produced according to a general method for producing a patch.
[0123] The adhesive layer can be formed by supplying an adhesive to one upper surface of a support or a peeling body, for example, by a coating method, an extrusion molding method, etc. In addition, the adhesive layer can be formed by supplying an adhesive between the support and the peeling body. Furthermore, the support and the adhesive layer can also be co-extruded.
[0124] From the viewpoint of being able to easily manufacture an adhesive material with stable quality, a method for manufacturing an adhesive material that includes the step of applying an adhesive to the upper surface of a peeling body layer to form an adhesive layer is preferred. The method for applying the adhesive is not particularly limited to solution coating, hot melt coating, emulsion coating, etc., and in particular, in the case of obtaining a thin adhesive layer with a thickness of less than 50 μm, a solution coating method is preferred. Specifically, while the pre-formed peeling body is moved in one direction, an adhesive for forming an adhesive layer is applied to its upper surface, and the adhesive layer is formed by drying and removing the solvent. Next, by stacking a support body in a manner such that the adhesive layer and the peeling body are opposite to each other, a patch material characterized in that a support body, an adhesive layer, and a peeling body are stacked in sequence can be obtained.
[0125] The coating pattern of the adhesive layer may cover the entire surface of the support or partially cover it. When partially covering, any pattern such as a lattice, a network, a granular, or an arabesque may be selected. By partially providing the adhesive layer on one side of the support, air permeability, moisture permeability, etc. can be further improved, and irritation when peeling from the skin can be further reduced.
[0126] When making this attached material, in order to improve the adhesion of this support and this adhesive layer, this support can also be subjected to surface treatment or primer treatment. As the surface treatment of this support, all known treatment methods such as embossing, sandblasting, corona discharge treatment, plasma treatment, alkali treatment can be adopted. As primer treatment, as long as, for example, a primer such as a primer containing a silane coupling agent, etc., which can be used in the composition of the present invention, all known primers can be used to carry out primer treatment.
[0127] <Purpose and usage of adhesive materials>
[0128] As described above, when the patch is attached to the skin, it can inhibit the stretching of the skin, so it can fully reduce the external force applied to the injured skin caused by trauma or surgery. In addition, it is also excellent in skin followability, moisture permeability, etc., so it can also be attached for a long time. Therefore, according to the patch material of the present invention, it is possible to promote the healing of wounds and the treatment of scars, and effectively prevent the formation of scars and keloids. It is especially effective for preventing the formation of scars and keloids. It can be suitably used to treat wound scars caused by surgical operations such as cesarean section, median sternotomy, laparoscopic surgery, or prevent the formation of scars / keloids. The direction (length direction and width direction) of the patch material when attached can be determined according to the size of the wound. In particular, when the wound is linear, it is preferably attached in a manner that the 10% tensile load in the direction perpendicular to the wound (the direction in which external force is easily applied) becomes higher. In addition, in addition to these uses, as long as it is a use that can give full play to the effect of the present invention, there is no special limitation. It can also be applied to affected areas such as eczema, burns, papules, ears, and BCG vaccinations.
[0129] In general, the wound healing process is one of the biological defense systems that is divided into three phases, namely, the inflammatory phase, the proliferation phase, and the tissue reconstructing phase, according to the passage of time. Mild wounds will heal naturally even without treatment. However, it can be inferred that if mechanical strains such as stretching are produced at the wound site, the apoptosis of necrotic tissue and superfluous cells digested and removed by macrophages in the early stage of the proliferation phase is inhibited, resulting in scarring of collagen fibers. As a result, the reconstruction of the tissue is inhibited, and the scar hypertrophies and forms a keloid. Therefore, the patch material of the present invention can be used to treat scars caused by trauma and surgery from the perspective of promoting wound healing. On the other hand, it can be used to prevent the formation of scars and keloids from the perspective of inhibiting the formation of scars and keloids.
[0130] The usage of the patch material can be appropriately selected according to the purpose. For example, in the case of preventing scars / keloids from forming on the wound, it is preferably applied continuously for about 3 to 12 months. After a patch material is temporarily applied, it can be applied continuously until it is peeled off. This period is usually about 3 to 10 days. Afterwards, a new patch material is applied, and after peeling, a new patch material is applied again, and it is expected that the above operation is repeated.
[0131] For waterproofing and long-term adhesion, the patch may be covered with a decorative material, medical tape or the like as needed.
[0132] Example
[0133] The present invention will be described in more detail below by way of examples, but the present invention is not limited thereto. Parts and % in the following examples and comparative examples represent parts by mass and % by mass, respectively, unless otherwise specified.
[0134] 《Production of attachment materials》
[0135] 1. Adhesive
[0136] As acrylic adhesives, acrylic adhesive 1 and acrylic adhesive 2 were used. Acrylic adhesive 1 was obtained by adding 0.3 parts by mass of Coronate (registered trademark) HL (manufactured by Nippon Polyurethane Industries) as a crosslinking agent to 100 parts by mass of an alkyl acrylate copolymer containing isononyl acrylate / 2-methoxyethyl acrylate / acrylic acid (mass ratio of 68 / 30 / 2). Acrylic adhesive 2 was obtained by adding 0.03 parts by mass of TETRAD-X (registered trademark) (manufactured by Mitsubishi Gas Chemical Co., Ltd.) as a crosslinking agent to 100 parts by mass of an alkyl acrylate copolymer containing isononyl acrylate / acrylic acid (mass ratio of 96 / 4).
[0137] 2. Support body
[0138] As support, used are:
[0139] PET woven fabric,
[0140] PET woven fabric + PU film laminate (a product obtained by laminating polyester woven fabric with polyurethane film),
[0141] A product obtained by coating one side of a PET woven fabric with a urethane resin,
[0142] PET film,
[0143] PP spunbond nonwoven fabric (polypropylene long fiber nonwoven fabric),
[0144] Polyurethane nonwoven fabric,
[0145] PET / Pulp Nonwoven Fabric (Nonwoven fabric containing polyester and pulp).
[0146] The above-mentioned PET woven fabrics were produced by the method shown below. Specifically, a false-twisted yarn (56 dtex / 36 yarns, stretch recovery (CR) of 36%, strength of 4.6 cN / dtex) obtained by false-twisting polyethylene terephthalate fibers (KB Seiren Co., Ltd., 84 dtex / 36 yarns, containing 0.3% by mass of titanium oxide) at a torque of 178 times / m was used to produce a plain knitted fabric (width 135 cm, warp density 102 yarns / inch (2.54 cm), weft density 90 yarns / inch (2.54 cm)), and the fabric was prepared under the conditions shown in Table 1 to produce each PET woven fabric. The width, weaving density, thickness, and unit weight of each PET woven fabric are shown in Table 1. In addition, the 1%, 5%, and 10% tensile loads of each PET woven fabric are shown in Table 2. The stretch recovery ratio (CR) of the false twisted yarn and the dimensions and properties of each PET woven fabric are measured as follows.
[0147] <Methods for measuring various properties of support body>
[0148] (Tensile load)
[0149] Tensile tests were conducted in accordance with JIS L1096, and 1%, 5%, and 10% tensile loads were measured. The test pieces of each attached material were cut into short strips of 25 mm wide and 100 mm long in the width (CD) direction and the length (MD) direction, respectively. Three test pieces were cut in the width (CD) direction and the length (MD) direction of each support, and all three were measured. The average value of the three test pieces was recorded as the measured value of the tensile load in the CD direction and the MD direction, respectively. If the measurement conditions are summarized, they are as follows.
[0150] Testing machine: AUTOGRAPH tensile testing machine
[0151] Test piece: 25mm wide, 100mm long
[0152] Clamping interval: 50mm
[0153] Crosshead moving speed (stretching speed): 300mm / min
[0154] Number of repeated trials: n = 3
[0155] (Weaving density)
[0156] The weaving density in each of the warp and weft directions was measured using a densitometer and recorded as the weaving density in the directions.
[0157] (thickness)
[0158] According to JIS L1085, the thickness after 10 seconds under pressure was measured at the four corners of a 250 mm×250 mm test piece using a thickness gauge (manufactured by Peacock, model: No. H), and the average value was taken as the measured value.
[0159] (Weight per unit area)
[0160] Three test pieces of 250 mm x 250 mm were taken, and the mass was measured to 10 mg, and the average value was multiplied by 16. The average value of the three test pieces was taken as the measured value.
[0161] (Recovery rate (CR))
[0162] A load of 0.176 mN × total fineness was applied, and a small reel with a reel length of about 40 cm and 10 winding times was made, and boiled at 100°C for 15 minutes. A load of 0.176 mN × 20 × total fineness was applied to the sample, and then a load of 8.82 mN × 20 × total fineness was applied, and after immersion in water at a temperature of 20 ± 2°C for 2 minutes, the reel length was measured, and the load of 8.82 mN × 20 × total fineness was immediately removed and left for 2 minutes, and then the reel length was measured again, and the expansion recovery rate (%) was calculated using the following formula.
[0163] E=(ab)×100 / a
[0164] E = expansion recovery rate (%)
[0165] The length of the bobbin when a load of 8.82 mN × 20 × total fineness is applied on the basis of a = = 0.176 mN × 20 × total fineness (mm)
[0166] Length of winding shaft when load b=0.176mN×20×total fineness is applied (mm) [Table 1]
[0167] [Table 1]
[0168]
[0169] [Table 2]
[0170] [Table 2]
[0171]
[0172] 3. Production of attachment materials
[0173] [Examples 7 to 12 and Comparative Examples 1 to 6]
[0174] An ethyl acetate solution of an acrylic adhesive (the total solid content is about 40% by mass) is prepared to a thickness of 40 g / m 2The adhesive layer was applied to one side of the peeling body in a manner of , and then dried to form an adhesive layer, and then laminated to each support to produce an adhesive material. The acrylic adhesive and support used are shown in Table 3. The properties of the obtained adhesive material were measured using the method described below and are shown in Tables 4 to 8. It should be noted that "-" in Table 6 means not implemented.
[0175] [Table 3]
[0176] [Table 3]
[0177]
[0178] <Methods for measuring various properties of patch materials>
[0179] (Tensile load)
[0180] The patch materials of the examples and comparative examples were subjected to tensile tests according to JI SK 7113, and the tensile loads of 1%, 5%, and 10% were measured. The test pieces of each patch material were obtained by cutting short strips of 25 mm in width and 100 mm in length in the width (CD) direction and the length (MD) direction. Cloth adhesive tape manufactured by NICHIBAN was attached to both ends so that the clamp interval was 50 mm. <ls>No.123, prepare a test piece for tensile strength measurement, and install it on the crosshead of a TENSILON type tensile testing machine with the aforementioned clamping interval of 50mm. Pull up the upper crosshead at a speed of 300mm / min to stretch the aforementioned test piece. The measurement conditions for stretching are set to "the origin of stretching is the initial load point, the initial load value is 3.0N, and the relaxation is not corrected", and the loads when stretched to 1%, 5%, and 10% are recorded as 1%, 5%, and 10% tensile loads, respectively. The unit of tensile load is expressed in Newton (N) / 25mm. Cut 3 test pieces in the width (CD) direction and the length (MD) direction of each attached material, and perform the aforementioned measurement on all 3 pieces. The average value of the 3 test pieces is recorded as the measured value of the tensile load in the CD direction and the MD direction. If the measurement conditions are summarized, it will be as follows.
[0181] Testing machine: TENSILON tensile testing machine
[0182] Test piece: 25mm wide, 100mm long
[0183] Clamping interval: 50mm
[0184] Crosshead moving speed (stretching speed): 300mm / min
[0185] Number of repeated trials: n = 3
[0186] Measurement atmosphere: 23°C, 50% RH
[0187] (Stiffness)
[0188] The cantilever test is based on JIS L 1096. The test pieces of each attached material are prepared by cutting into short strips of 20 mm wide and 150 mm long in the width (CD) direction and the length (MD) direction, respectively. On a horizontal platform with a 45° slope and a smooth surface, the short side of the sample is placed in conjunction with the baseline of the ruler, and the test piece is slowly slid along the direction of the slope using an appropriate method. When the test piece falls over within 20 seconds, the end position of the horizontal platform side is read by the ruler. The stiffness is expressed by the moving length (mm) of the test piece, and the average value of the three test pieces is recorded as the measured value of the stiffness. It should be noted that all measurements are carried out with the supporting body of each attached material facing downward.
[0189] (Apparent density)
[0190] Calculate the unit area weight (g / m 2 ) divided by its thickness (μm) is recorded as the apparent density (g / cm 3 ).
[0191] (Moisture Permeability)
[0192] The moisture permeability was measured under the conditions of 40°C and 90% relative humidity according to the B condition of JIS Z 0208. That is, one side of each patch was adjusted to 40°C and 90% relative humidity, and about 15g of a moisture absorbent (calcium chloride) was placed on the other side to absorb the moisture passing through each patch. The mass change of the moisture absorbent was converted into 1m 2 , averaged over 24 hours, and the average value of the three test pieces was recorded as the moisture permeability.
[0193] (Possibility of drug delivery from patch material)
[0194] Evaluate whether drug delivery from the patch is possible.
[0195] Two patches cut into 25 mm wide and 100 mm long were attached to the lower part of the navel, and 0.5 g of ointment (Rinderon VG ointment 0.12%: manufactured by Shionogi Pharmaceutical Co., Ltd.) and paste (Rinderon VG paste 0.12%: manufactured by Shionogi Pharmaceutical Co., Ltd.) were applied to each of the two patches on the side of the support body that was not coated with the adhesive. After that, the patch was peeled off, and it was visually confirmed whether the ointment was applied to the skin. If it was applied, it was evaluated as A, and if it was not applied, it was evaluated as D. The test was carried out on 3 people, and the evaluation of 2 or more people was recorded as the evaluation of this test.
[0196] (elongation recovery rate)
[0197] The test pieces of each adhesive material were cut into short strips of 25 mm in width and 100 mm in length in the CD and MD directions. Cloth adhesive tape manufactured by NICHIBAN was attached to both ends with a clamping interval of 50 mm. <ls>No. 123, prepare a test piece for tensile strength measurement, and install it on the crosshead of the TENSILON type tensile tester with the aforementioned 50mm (L0) marked. Pull the upper crosshead at a speed of 300mm / min, and measure the tape length (L1) when a 9N (or 18N) load is applied to the test piece. Afterwards, after the displacement returns to zero (load removed), when a 9N (or 18N) load is applied, measure the length of the clamp gap when the load is started (L2), and calculate it by the following formula.
[0198] Elongation recovery rate (%) = {(L1-L2) / (L1-L0)}×100
[0199] Three test pieces were cut from each patch material in the width (CD) direction and the length (MD) direction, and the above measurements were performed on all three test pieces. The average value of the three test pieces was recorded as the measured value of the elongation recovery rate in the CD direction and the MD direction. The measurement conditions are as follows.
[0200] Testing machine: TENSILON tensile testing machine
[0201] Test piece: 25mm wide, 80mm long
[0202] Clamp spacing: 50mm
[0203] Crosshead moving speed (stretching speed): 300mm / min
[0204] Number of repeated trials: n = 3
[0205] Measurement atmosphere: 23°C, 50% RH
[0206] [Table 4] [Table 4]
[0207]
[0208] [Table 5] [Table 5]
[0209]
[0210] [Table 6]
[0211] [Table 6]
[0212]
[0213] <Evaluation method of patch material (evaluation for practical application to human skin)>
[0214] Each patch was applied to the following parts of human skin and evaluated according to the following method. It should be noted that three test pieces of each patch cut into 50 mm squares in the width (CD) direction and the length (MD) direction were used for evaluation at each part.
[0215] (below the navel)
[0216] Use a marker to mark a 50mm square (4 sides of 50mm x 50mm) below the navel. The vertical (up and down) direction of the body is recorded as the longitudinal direction, and the horizontal (left and right) direction is recorded as the transverse direction (the same is true for the chest and shoulders). Put your hands on your hips, stand still with your waist bent backwards (leaning back), and measure the length of the marked longitudinal side at this time (the behavior of stretching the skin). In addition, stand still in a state of bending over and sitting on a chair, and measure the length of the marked transverse side at this time (the behavior of contracting the skin). These measured values are used as the measured values when not attached (blank). Next, attach the test piece of each attached material to the marked part, perform the same action, and use a tape measure to measure the longitudinal length of the tape as the measured value when attached. Perform the same measurement on the 3 test pieces of each attached material. The difference between the measured value when not attached and the measured value when attached and the initial value (50 mm) was calculated respectively, and the extent to which the stretched length or contracted length when not attached was suppressed when attached was calculated as the suppression rate (%), and evaluated according to the following evaluation criteria. Only the longitudinal evaluation results are shown in Table 4. It should be noted that the results shown in Table 4 are the average values for the above-mentioned 3 test pieces. Here, a suppression rate of 100% means that the stretching of the skin is completely suppressed by attaching the patch material.
[0217] (Chest)
[0218] Use a marker to mark a 50mm square (4 sides of 50mm×50mm) on the frequently moved part of the chest (center of the chest). Make fists with both hands, expand the chest by pushing it forward, and remain still in this state (stretching the skin). Measure the length of the marked vertical and horizontal sides at this time, and record it as the measured value when not attached (blank). Next, attach the test piece of each patch material to the marked part, perform the same action, and use a tape measure to measure the length of the vertical and horizontal sides of the tape, and record it as the measured value when attached. Perform the same measurement on 3 test pieces of each patch material in the width (CD) direction and 3 in the length (MD) direction. The calculation of the inhibition rate is carried out in the same way as in the case of the navel, and is evaluated according to the following evaluation criteria. The results are shown in Table 5.
[0219] (Evaluation Criteria)
[0220] Targeting the behavior of stretching the skin
[0221] A: Inhibition rate is 100% to 90%
[0222] B: Inhibition rate is 89% to 80%
[0223] C: Inhibition rate is 79% to 70%
[0224] D: Inhibition rate is less than 69%
[0225] [Table 7]
[0226] [Table 7]
[0227]
[0228] <Evaluation method of patch material (evaluation after continuous application on human skin for 5 days)>
[0229] Each patch material was attached to the abdomen of human skin and evaluated according to the following method. It should be noted that in the evaluation at each site, one test piece obtained by cutting each patch material into a size of 50 mm square in the width (CD) direction and the length (MD) direction was attached to the abdomen for 5 consecutive days to evaluate adhesion, itching during attachment, discomfort during attachment, pain during peeling, and skin irritation after 1 hour and 24 hours after peeling.
[0230] (Adhesion)
[0231] The adhesion area ratio was calculated and the average score was used as the evaluation result.
[0232] (itch)
[0233] 100: No itch
[0234] 60: Slightly itchy, but no problem
[0235] 0: Itchy, becomes a problem
[0236] (Discomfort)
[0237] 100: No discomfort
[0238] 60: Slightly uncomfortable, but no problem
[0239] 0: Discomfort exists and becomes a problem
[0240] (Skin irritation 1 hour and 24 hours after peeling)
[0241] 100: No skin irritation
[0242] 60: Slight skin irritation, but no problem
[0243] 0: Skin irritation is a problem
[0244] (evaluate)
[0245] Adhesion, itching during application, discomfort during application, pain during application, and skin irritation 1 hour and 24 hours after removal were scored according to the above criteria and evaluated as follows.
[0246] A: 100-90
[0247] B: 89-80
[0248] C: 79-70
[0249] D: 69 or below
[0250] [Table 8]
[0251] [Table 8]
[0252]
[0253] <Evaluation>
[0254] As shown in Tables 4 to 8 above, it can be seen that the patch materials of the examples can fully suppress the stretching of the skin. In addition, the adhesion rate of the patch materials of the examples to the skin is high after 5 days of application, and there is almost no itching or discomfort during the application process. Furthermore, there is little skin irritation after peeling. As shown in this way, the patch materials of the examples are excellent in the effect of suppressing skin stretching, and are also excellent in followability to the skin, and can be applied for a long time. Specifically, the patch materials of the examples stretch following the slight movement during application (1% tensile load is small), and suppress the movement that affects the formation of scars / keloids (10% tensile load is large). In contrast, it can be seen that even if the patch materials of the comparative examples are excellent in the characteristic evaluation in Table 8, the effect of suppressing skin stretching shown in Table 7 is not sufficient, and it is impossible to achieve both the effect of suppressing skin stretching and the followability to the skin. In particular, in the PET films of Comparative Examples 1 to 3, the 1% tensile load is large, and they do not follow the slight movement during application, and there are many cases where discomfort is felt or they are easy to peel off during application. In the nonwoven fabrics of Comparative Examples 4 to 6, although they follow the slight movement during attachment, most of them do not suppress the movement that affects the formation of scars / keloids (10% tensile load is small). It can be seen that: 10% tensile strength affects the inhibition of stretching, 1% tensile strength, stiffness, and the product of stiffness and apparent density affect adhesion and discomfort, and moisture permeability affects itching and skin irritation during attachment. It should be noted that sometimes the measured value of the tensile load of the support itself and the attached material using the support is quite different. It is considered that this is mainly due to the changes in the physical properties of the support caused by the tension and heat applied to the support when applying the adhesive, and the heating when the adhesive matures.
[0255] Industrial Applicability
[0256] The wound covering material or postoperative wound protection patch of the present invention can appropriately suppress the stretching of the skin according to the applied stress, so that the external force applied to the wounded skin caused by trauma or surgery can be fully reduced, and the skin followability and moisture permeability are also excellent. Therefore, it can also be attached for a long time. Therefore, the wound covering material or postoperative wound protection patch of the present invention is suitable for healing wounds, for treating scars, or for preventing the formation of scars and keloids.< / ls> < / ls>
Claims
1. A patch for wound covering or postoperative wound protection, comprising a support and an adhesive layer provided on one side of the support, The patch has a 1% tensile load of 13 N / 25 mm or less in the longitudinal direction and the width direction, and a 10% tensile load of 18 N / 25 mm or more and 95 N / 25 mm or less.
2. The patch material according to claim 1, wherein: The stiffness of the patch material is greater than or equal to 5 mm and less than or equal to 40 mm, and the unit of the stiffness is mm.
3. The patch material according to claim 1 or 2, wherein: The 5% tensile load of the patch material is greater than or equal to 5 N / 25 mm and less than or equal to 50 N / 25 mm.
4. The patch according to any one of claims 1 to 3, wherein the product of the stiffness and the apparent density by the cantilever method is 2 or more and 30 or less, The unit of stiffness is mm, and the unit of apparent density is g / cm 3 .
5. The patch material according to any one of claims 1 to 4, wherein The support body comprises a woven fabric.
6. The patch material according to any one of claims 1 to 5, wherein The moisture permeability of the attached material is 1000g / m 2 ·More than 24h, The unit of moisture permeability is g / m 2 ·24h.
7. The patch material according to any one of claims 1 to 6, wherein The elongation recovery rate of the patch material under a load of 9N or 18N in at least one of the longitudinal direction or the width direction is 85% or more. 8 . The patch according to claim 1 , wherein the drug required for the patch can be applied to an affected area such as a wound from an upper portion of the patch.
9. The patch according to any one of claims 1 to 8, which is used for healing wounds, for treating scars, or for preventing the formation of scars / keloids.
10. The patch according to claim 9, which is used for healing wounds caused by surgical operations, for treating scars, or for preventing the formation of scars / keloids.
11. The patch material according to claim 10, wherein: The surgical procedure is cesarean section, median sternotomy or laparoscopic surgery.
12. A patch material comprising a support and an adhesive layer provided on one side of the support, The 1% tensile load in the length direction and the width direction of the patch material is 13N / 25mm or less, the 5% tensile load is 5N / 25mm or more and 50N / 25mm or less, and the 10% tensile load is 18N / 25mm or more and 95N / 25mm or less, the support body comprises a woven fabric, and the adhesive layer comprises a foamed acrylic adhesive, The patch material is used for healing wounds caused by surgical operations, for treating scars, or for preventing the formation of scars / keloids.
13. A patch material comprising a support and an adhesive layer provided on one side of the support, The 1% tensile load of the attached material in the length direction and the width direction is 13N / 25mm or less, the 5% tensile load is 5N / 25mm or more and 50N / 25mm or less, and the 10% tensile load is 18N / 25mm or more and 95N / 25mm or less, the stiffness of the attached material is 8mm or more and 25mm or less, and the attached material includes a shape having one or more concave or convex portions on the side portion clamped by the two ends in the length direction or the width direction, The patch material is used to heal wounds caused by surgical operations, to treat scars, or to prevent the formation of scars / keloids. The unit of the stiffness is mm.
14. The patch according to claim 12 or 13, wherein the medicine required for the patch can be applied to an affected area such as a wound from the upper portion of the patch.
15. A support body for an adhesive patch material, which is used as a support body for an adhesive patch material for wound covering or postoperative wound protection, wherein the 1% tensile load in the length direction and the width direction of the support body is less than 13N / 25mm, and the 10% tensile load is greater than 15N / 25mm and less than 95N / 25mm.
16. The patch support according to claim 15, wherein: The support is a woven fabric using yarns having a total fineness of 40 dtex or more and 85 dtex or less, and having a warp density of 80 to 120 yarns / inch and a weft density of 80 to 120 yarns / inch, 1 inch is 2.54 cm.
17. The patch support according to claim 15, which is a woven fabric using false twisted yarn having a total fineness of 40 dtex or more and 85 dtex or less and a stretch recovery ratio CR of 15 to 40%.
